ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN DI PROVINSI PAPUA - Muhammad, Rafly Izza; Vidriza, Ullya (Journal of Economics and Regional Science, 2026)
This study aims to analyze the effect of the Open Unemployment Rate, CPI, and Economic Growth on poverty in Papua Province for the period 1993-2023. Papua Province is the province with the highest poverty rate in Indonesia. The data used is secondary data with an annual frequency obtained from the Central Statistics Agency (BPS). The analysis method used is the Vector Error Correction Model (VECM) to analyze the short-term and long-term relationships between variables. The results show that in the long run, the open unemployment rate, consumer price index, and economic growth have a significant positive effect. In the short term, the variable shows a significant positive effect on poverty in Papua Province, while the consumer price index variable, and economic growth have no significant effect on poverty in Papua Province.